Super Rice With High Sink Activities Has Superior Adaptability to Low Filling Stage Temperature - Xu, Congshan; Yang, Fei; Tang, Xinao; Lu, Bo; Li, Ziyu; Liu, Zhenghui; Ding, Yanfeng; Ding, Chao; Li, Ganghua (Frontiers in Plant Science, 2021)
To investigate the differential responses of super rice grain filling to low filling stage temperature (LT) and the regulative effect of nitrogen panicle fertilizer (NPF), physiological and molecular experiments were conducted with two super rice varieties (Nanjing 7th: N7 and Nanjing 9108th: N9108) on two different filling stage temperature treatments implemented by applying two sowing dates [Normal filling stage temperature (CK): Sowed on May 30, Tmean = 24.7°C and low filling stage temperature (LT): Sowed on July 1, Tmean = 20.3°C], and two NPF levels (0 and 150 kg N ha−1). In this study, LT, NPF, and simultaneous LT and NPF treatments suppressed the grain filling in all varieties with different levels. Under LT or NPF treatments, the reduction of grain weight, seed setting rate, and filling rate were closely associated with suppressed starch biosynthesis rate in inferior seeds, suggesting that reduced starch biosynthesis rate, expression, and activities of enzymes encoded by related genes, Floury endosperm-4 (FLO4), Starch branching enzyme-I (SBE1), and Starch phosphorylase-L (PHO-l), were responsible for the grain filling reduction. Under LT or NPF treatments, significantly higher grain filling rates and lower variance were found in N9108 compared to that in N7, which were closely related to their higher starch biosynthesis ability, related gene expression, and enzymes activities. One of the probable explanations of the grain filling difference was the variation in the relative amount of key regulative hormones, Abscisic acid (ABA) and 1-aminocyclopropane-1-carboxylic acid (ACC). These results raise a possibility that super rice with higher sink activities has superior adaptability to LT and NPF due to their higher sink activities.